Sistem Informasi Geografis Pemetaan Keluarga Pra Sejahtera Di Desa Pandak Kecamatan Masamba Kabupaten Luwu Utara Menggunakan WebGIS - Nur’ain Nur’ain (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
WebGIS is an information system used to convey information equipped with digital maps.Pre-rous families are measured using the concept of the ability to meet basic needs (basic needs approach).The aim of this research is to determine the locations of families that are classified as pre - trade indicators and make it easier for village governments to map community data.This research uses the Research and Development (R&D) method.The classic method that is still maintained by the Pandak Village should undergo changes in order to create progress and prosperity.